Conjecturing Ability Dalam Pembelajaran Daring Masa Pandemi Covid-19 - Yani Supriani; Giyanti; Tb. Sofwan Hadi (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2020)
Learning was done online during the COVID-19 pandemic; it inhibits the development of mathematical cognitive abilities, whereas this ability supports the learning skills of students in mathematics. One of the cognitive gained is the conjecturing ability or the ability to formulate the mathematical conjecture of junior high school students. The conjecture is the reason that someone has a belief, interpretation of why a belief is true, or how someone knows what he knows. So it is necessary to do an in-depth study and analysis of students’ mathematical conjecturing abilities. This study involved 26 students in one of junior high school in Serang as the research subjects, the approach used is a qualitative approach. The finding shows that the students’ conjecturing ability is still worse in the category of students’ ability in making evidence to the solution, so it needs improvement from the poor of students’ mathematical conjecturing abilities.